Direct and indirect effects of received social support on athletic mental energy: Testing burnout as a mediator among student-athletes - Gideon Juezan; Ivan Jee Juezan; Joseph Lobo (CV. FOUNDAE, 2026)
Background: Athletic mental energy is an important sport-specific psychological resource that supports athletes’ motivation, focus, confidence, and readiness during training and competition. However, its social and psychological correlates remain underexamined in regional collegiate sport contexts in the Philippines. Aims: This study examined the statistical associations among received social support, burnout, and athletic mental energy among collegiate student-athletes in Region XI, Philippines, and tested burnout as a possible indirect pathway between received social support and athletic mental energy. Methods: A quantitative, non-experimental correlational design with mediation analysis was employed. Participants were 280 collegiate student-athletes selected through systematic random sampling. Data were gathered using the Athletes’ Received Support Questionnaire, Athlete Burnout Questionnaire, and Athletic Mental Energy Scale. Mediation analysis was conducted using Hayes’ PROCESS macro Model 4 in SPSS with 5,000 bootstrap resamples. Result: Received social support was significantly and positively associated with athletic mental energy (B = 0.123, p = .009). Burnout was not significantly associated with athletic mental energy (p = .061), and the indirect pathway through burnout was not significant. Conclusion: The findings suggest that received social support is directly associated with higher athletic mental energy among collegiate student-athletes, while burnout did not statistically explain this association. Strengthening responsive support systems may help sustain athletes’ psychological readiness in collegiate sport settings.